Evaluation of Herpes, Cytomegalovirus, Rubella, and Toxoplasma Gondii Infections in Swabi, KPK, Pakistan - Fawad Mahmood, Mehwish Zafar, Sarwat Noreen, Sahiba Gul, Ikram Ullah, Saima Khattak (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Toxoplasma gondii (TG), Rubella virus (RV), Cytomegalovirus (CMV), and Herpes simplex virus (HSV) 1 and 2, globally most neonatal and infant deaths are reported due to this group of infections. Purpose: The objective of this research study is to estimate the Prevalence of TORCH infections. Methods: This research study was carried out at the Hi-Tech clinical laboratory Shewa Adda Swabi KPK Pakistan for a duration of 4 months from April 2022 to July 2022. Data statistics looking at the clinical characteristics of Toxoplasma gondii, CMV, RV, and HSV were filled from n=371. All samples were qualitative and quantitative tested by using Immune chromatographic (ICT) and Chemiluminescence Microparticle Immunoassay (CMIA) techniques. Results: Out of n=317 pregnant women, n=131 (35 %) women were found positive while n=240 (65 %) women were found negative. Prevalence of Toxoplasma gondi 32 %, RV 28 %, CMV 27 %, and HSV 13 % in Swabi, KPK, and Pakistan. Among them, a high-frequency fraction of co-infection was detected for CMV and Rubella 17 (58 %), followed by CMV, Herpes, Rubella virus, and Toxoplasma gondii combined 7(25 %). The highest number of infected individuals 37 % we found in the age-group 21-25 years, followed by the 15-20 years age group 23 %, 26-30 years age group 17 %, 31-35 years age group 23 % while the lowest number of positive individuals found in >36 age group. Conclusion: In brief context, TORCH pathogens have potentially shocking clinical manifestations. Hence, screening before pregnancy, and timely diagnosis of TORCH can reduce disease and death in both kid, and the mother. Moreover, knowing the epidemiology survey is a significant aspect to develop strategies and implementation for the prevention of disease. Keywords: Pregnancy, Prevalence, TORCH, Swabi, Infections.